'Reflections facilitate emotions and emotions filter reflections': beginning teachers' perceptions of affective reflective practices. Issue 1 (2nd January 2023) - Arefian, Mohammad Hossein
ABSTRACT: Besides numerous positive feelings experienced during first practices, beginning teachers sometimes face challenges, experiences, and situations that produce negative emotions that can lead to attrition and burnout. Thus, the purpose of this study is to investigate how beginning teachers' affective reflective practices can be a great tool for monitoring emotional flows and taking action to solve them, and making emotional actions more logical and systematic. This study explored 17 Iranian English as a Foreign Language (EFL) beginning teachers' perceptions of emotional-reflective practices. Through a qualitative research design, the result from interviews and thematic analysis revealed that beginning teachers could use reflections to facilitate emotions, be autonomous in controlling their emotional flows, become rational decision-makers, monitor their practices impartially, have self-understanding and self-awareness, and encourage themselves continuously. Also, emotions can influence and act as a filter for reflections, so teachers can control their emotions to have a valid and reliable reflection; in this case, they can make reflections more systematic. This study opens a new approach to reflections for beginning teachers and makes teacher educators and stakeholders aware of its benefits.